Simulation of Unsymmetrical Parameters Two-Phase Induction Motor Drive Based on Rotor Field Orientation Control Strategy - Charumit, Chakrapong; Jitson, Tawatchai; Pattanapong, Yongyut (Journal of Advanced Development in Engineering and Science, 2023)
This paper presents a simulation of unsymmetrical parameter two-phase induction motor control using indirect rotor field orientation control (IFOC) strategy. The proposed two-phase induction motor simulation is modified from the single-phase induction motor in type of capacitor start and run motor with the operating parameters including 1 hp, 4 pole, 220V, 5.2A and 1430 rpm. The calculation of parameters for IFOC such as rotor flux orientation, slip speed, current for flux and torque producing in rotating reference frame is proposed. The two-phase three-leg voltage source inverter using current control technique or constant hysteresis band control technique is used. The simulation results of the proposed method emphasize the static and dynamic performance improving while the load torque is changed. The simulation results of unbalanced parameter two-phase induction motor can be achieved for high motor performance.